Efektivitas dan Keberterimaan Madcom Noise Protection sebagai Alat Pelindung Pendengaran Berbasis Perlindungan Ganda - Ramadhan, Ahmad Athif Wahyu; Yamtana, Yamtana; Dyah Prasetyawati, Naris; Sudaryanto, Sigid (UI Scholars Hub, 2025)
Industrial environments often generate high noise levels due to the continuous operation of machinery and production equipment. Persistent exposure to workplace noise exceeding the Threshold Limit Value (TLV) can lead to noise-induced hearing loss. According to the World Health Organization, an estimated 430 million people worldwide require rehabilitation for hearing impairment, with 109.4 million of these cases occurring in Southeast and Central Asia. As a critical component of Occupational Health and Safety (OHS) management, noise control is often implemented using Hearing Protection Devices (HPDs). This study aims to evaluate the effectiveness of an earplug-earmuff combination, developed as Madcom Noise Protection, in enhancing noise attenuation and assessing its acceptability among users. Utilizing a quasi-experimental design, the study involved 30 students from Poltekkes Kemenkes Yogyakarta. The results demonstrate that Madcom Noise Protection significantly improved hearing threshold levels by an average of 8.50 dB compared to using an earmuff alone (p < 0.001). Furthermore, user acceptability was remarkably high, reaching an average score of 97.33%. In conclusion, the developed earplug-earmuff combination is highly effective in strengthening hearing protection and is well-received as an innovative HPD modification. Keywords: Noise, Hearing Protection Devices (HPDs), Earplug-Earmuff, Madcom Noise Protection